Wind Resource for Electrical Energy of Tourism and Micro Small and Medium Enterprises (MSMEs) in Coastal Areas After the COVID-19 Pandemic - Siagian, Parlin (Adpebi International Journal of Multidisciplinary Sciences, 2022)
The abstract should be clear and informative in one paragraph (between 150 and 250 words). Use Times New Romans font in size 10. Purpose – This paper seeks to examine the The strategy to growth economical in coastal area that’s one of the areas more lovely designed to be a tourist destination in which is quite attractive to tourists, especially domestic tourists. The coastal area which is a fairly wide open landscape in the coastal area is very good for a source of wind energy that continues to feel the wind. Wind speed potential is used for wind power plant design data. In connection with many home industries that have started after Covid-19 Pandemic the independent use electrical energy, is one key to growth, so a source of electrical energy is needed that can be generated from the potential that exists around the community. Methodology/approach – One way to increase MSMEs income is to reduce the cost of electrical energy for business needs. Electrical energy is obtained independently by utilizing the potential of its primary energy source, namely wind, which is quite large in coastal areas. To obtain wind potential data, data is collected using equipment that is adapted to the final destination in the form of place and time. Anemometer equipment is used to obtain wind speed data so that the condition of the wind speed in a place can be known. Findings – It was found that The potential wind generated will be the basis for the design that will be used to design a wind turbine suitable for power generation. At that hour the wind has a speed of 2 m/s - 5 m/s. Effective hour that can operating turbine while wind speed flow continue in 10.00 AM until 04.00 AM day tomorrow. The existing wind speed will be adjusted according to the design of the turbine that will be used. Novelty/value – Electrical energy from wind resources in coastal areas can save the cost of electricity needs for growing SMEs. Savings in electricity needs are obtained from wind turbines that can rotate at low speeds.